How, when, and to what degree do people with alcohol dependence recover their psychological wellbeing and quality of life? The Madrid Recovery Project - Rubio, Gabriel; Esteban Rodríguez, Laura; Sion, Ana; Ramis Vidal, Lilian; Blanco, María J.; Zamora-Bayon, Amelia; Caba-Moreno, Marta; Macias-Molina, Ana I.; Pérez-Sánchez, Dolores; Rubio-Escobar, Enrique; Ruiz-Diez, Joaquín; Marin, Marta; et al. (Frontiers in Psychiatry, 2023)
Introduction The consensus on recovery from alcohol use disorder (AUD) has shifted toward encompassing psychological wellbeing and quality of life dimensions. However, few studies have explored the long-term recovery process and its dimensions, timing, styles, and modes. The aim of this study was to investigate the extent, timing, and process of psychological wellbeing and quality of life recovery in alcohol use disorder (AUD) patients, as well as the relationship with classic dimensions of AUD recovery. Method A cross-sectional study has been carried out with 348 participants with AUD, in different abstinence periods (1 month–28 years), and 171 control subjects. Participants underwent a psychological evaluation, which included self-informed measures of psychological wellbeing, quality of life, negative emotionality, and coping strategies related to alcohol consumption avoidance. Statistical analysis included linear and non-linear regression models between psychological dimensions and maintenance of abstinence, as well as matching the scores of the sample with AUD to those of controls. Scatter plots were used to explore inflection points. In addition, mean comparison tests were performed between participants with AUD and controls and by gender. Results In general, according to the regression models, there were pronounced increases in indices of wellbeing and coping strategies (and pronounced decreases in negative emotionality) during the first 5 years of abstinence, followed by less pronounced improvements. The matching of AUD subjects in wellbeing and negative emotionality indices with controls occurs at different times: (a) 1 year or less: physical health; (b) 1–4 years: psychological health; (c) 4–10 years: social relationships, wellbeing, and negative emotionality; and (d) more than 10 years: autonomy and self-acceptance. There are statistically significant differences by gender for the negative emotionality and physical health variables. Conclusion Recovery from AUD is a long process that involves improvements in wellbeing and quality of life. Four stages can be described in this process, with the most pronounced changes occurring during the first 5 years of abstinence. However, AUD patients take more time to obtain similar scores to controls in several psychological dimensions.